Assessing microbial growth in drinking water using nucleic acid content and flow cytometry fingerprinting - Claveau, Leïla; Hudson, Neil; Jeffrey, Paul; Hassard, Francis (Elsevier, 2024)
This study utilizes flow cytometry (FCM) to evaluate the high nucleic acid (HNA) and low nucleic acid (LNA) content of intact cells for monitoring bacterial dynamics in drinking water treatment and supply systems. Our findings indicate that chlorine and nutrients differently impact components of bacterial populations. HNA bacteria, characterized by high metabolic rates, quickly react to nutrient alterations, making them suitable indicators of growth under varying water treatment and supply conditions. Conversely, LNA bacteria adapt to environments with stable, slowly degradable organics, reflecting distinct physiological characteristics. Changes in water treatment and supply conditions, such as chlorine dosing and nutrient inputs, significantly impact the ratio between HNA and LNA. FCM fingerprinting combined with cluster analysis provides a more sensitive evaluation of water quality by capturing a broader range of microbial characteristics compared to using only HNA/LNA ratios. This work advocates for multi-parameter data analysis to advance monitoring techniques for water treatment and supply processes.
Keywords: 3107 Microbiology; 31 Biological Sciences; 6 Clean Water and Sanitation